Evaluation of Online Learning Implementation During Covid-19 Pandemic for Sustainable Education in the Higher Education Level - Ediyanto Ediyanto; Atika Iva Nandya; Utomo Hari Widi; Konita Ardiana Pangestika; Handaka Irvan Budhi; Saat Rohaida Mohd (Discourse and Communication for Sustainable Education)
In the Covid-19 pandemic, starting from early 2020, technology has a vital role in education. During this pandemic, the learning process is carried out online, regardless of its positive and negative effects toward sustainable education. In an attempt to reduce the adverse effects, this study evaluated online learning by involving students. This study used a survey method and purposive sampling technique. The obtained data were analyzed and tested using the one-way ANOVA test. In collecting the data, we distributed a questionnaire to the Special Education Program students of Universitas Negeri Malang. Our survey results signified that 68.4% of participants were pleased with online learning, while the remaining 31.6% of participants were less satisfied with the assistance provided during online learning. Besides, we also observed different students’ satisfaction levels based on their gender. From our data analysis results, it is known that the female students tended to have higher satisfaction than the male students.